(untitled) (Research, Society and Development, 2021)
Cleft lip and palate are congenital malformations originated from the lack of fusion of the maxillary and midnasal processes. Children with these defects have facial anatomical impairment, which can prevent or hinder the performance of important functions, including breastfeeding. In this context, the multidisciplinary surgical treatment of cleft lip and palate is essential for the health of the child with orofacial anomaly and for a good maternal-infant relationship. In newborns, less invasive treatments can efficiently contribute to the adequate nutrition of the child until the correction surgery is performed, such as acetate plates, which act as a resource to occlude the fissure, facilitating suction, breathing, avoiding episodes of regurgitation and favoring orofacial growth. The objective and case report: the objective of this article is to report the case of a baby with cleft lip and palate, who had difficulties in adequate feeding due to the inefficient adaptation of the oral cavity with the maternal breast. Due to the patient’s young age, requiring the wait for the surgical procedure, it was chosen to make a flexible palatal obturator plate in order to occlude the cleft of the palate and allow the correct breastfeeding. This apparatus was made, after previous molding of the patient’s oral cavity, in the palate region, with EVA (Ethylene Copolymer/Vinyl Acetate), showing good adaptation and correct performance of the desired functions. Conclusion: the flexible palatal obturator plate is an effective and safe option of therapy for breastfeeding children with cleft lip and palate who are not old enough for surgical correction of the orofacial defect.